Primary and secondary effects of nocturnal traffic noise with different audio frequencies on sleep - Karjalainen, Saana (fi=Turun yliopisto|en=University of Turku|, 2017)
Nocturnal traffic noise disturbs sleep, causing arousals, sleep stage modifications, awakenings, increased body movements and experience of poor sleep quality. It has not, however, been established which acoustical properties (e.g., sound pressure level, number of noise events, audio frequencies) are the most detrimental to sleep. Low frequency traffic noises and high frequency traffic noises have not been previously compared on their effects on sleep. The main aim of this study was to analyse primary and secondary effects of nocturnal traffic noise with different audio frequencies. Twenty-one healthy volunteers, aged 20–30 years, slept four consecutive weekday nights in a sleep laboratory. After a habituation night, the participants slept in three rooms, with the order of the rooms counterbalanced. Each of these rooms had their own noise conditions: 1) engine noise dominating (low frequency noise room, the LF Room), 2) tyre noise dominating (high frequency noise room, the HF Room), and 3) quiet (the Q Room). The noise levels in the LF Room and the HF Room were equal, 38 dBA, but the rooms had two very different audio frequency ranges. The primary and secondary effects of traffic noise were assessed with polysomnography, questionnaires and the Psychomotor Vigilance Test. Decrease in the amount of slow-wave sleep was observed during both nights with traffic noise compared to the quiet night. No other objectively measured primary effects were found. During the nights with traffic noise, participants were less satisfied with their sleep and evaluated having woken up more often than during the quiet night. Being exposed to traffic noise did not have any secondary effects, such as sleepiness, strain or performance deficits in the Psychomotor Vigilance Test in the following morning and evening. The high frequency noise condition was experienced as the most obtrusive noise environment for sleep. However, there were no differences between the low frequency and the high frequency noise conditions in objectively and subjectively assessed sleep quality or performance. Results from this study do not highlight that either low frequency noise or high frequency noise is more disturbing for sleep than the other.